2013
DOI: 10.1186/1479-5876-11-247
|View full text |Cite
|
Sign up to set email alerts
|

HLA-dependent tumour development: a role for tumour associate macrophages?

Abstract: HLA abnormalities on tumour cells for immune escape have been widely described. In addition, cellular components of the tumour microenvironment, in particular myeloid derived suppressor cells (MDSC) and alternatively activated M2 tumour-associated macrophages (TAMs), are involved in tumour promotion, progression, angiogenesis and suppression of anti-tumour immunity. However, the role of HLA in these activities is poorly understood. This review details MHC class I characteristics and describes MHC class I recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 144 publications
(161 reference statements)
0
50
0
Order By: Relevance
“…TAMs also express the checkpoint ligands CD80/86 (B7-1/2) that inhibit TILs through binding CTLA4 [77]. In some cancer models, surface expression of specific MHC class I proteins can activate or suppress effector immune cells, with macrophage expression of less common HLA-G and E demonstrating ability to suppress T and NK cell function [78]. TAMs also secrete immunosuppressive cytokines IL-1β, IL-6, IL-10, and TGFβ [74].…”
Section: Discussionmentioning
confidence: 99%
“…TAMs also express the checkpoint ligands CD80/86 (B7-1/2) that inhibit TILs through binding CTLA4 [77]. In some cancer models, surface expression of specific MHC class I proteins can activate or suppress effector immune cells, with macrophage expression of less common HLA-G and E demonstrating ability to suppress T and NK cell function [78]. TAMs also secrete immunosuppressive cytokines IL-1β, IL-6, IL-10, and TGFβ [74].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, we showed that the high expression of another immune‐related gene, HLA‐A , was associated with prolonged survival in patients with ER−/HER2− tumors. HLA‐A belongs to the classical HLA class I (HLA‐I) family, which modulates the function of the tumor‐immune microenvironment, having a key role in cancer development orchestrated by tumor‐associated macrophages and immune recognition of cancer cells by cytotoxic T lymphocytes (CTLs) . The downregulation of HLA‐I expression by epigenetic silencing has been involved in tumor escape from immune surveillance, and has been reported in several types of human cancer, including BC .…”
Section: Discussionmentioning
confidence: 99%
“…Among these, we may find the derivative gpUL40 leader sequence of two human cytomegalovirus (HCMV) strains, peptides derived from the human immunodeficiency virus (HIV) gag protein, the Epstein-Barr virus (EBV) BZLF-1 protein, the influenza matrix protein and the Hepatitis C virus (HCV) core protein [7][8][9]. The binding of HLA-E with these viral peptides can trigger an escape mechanism of the innate immune response by inhibiting the NK cell-mediated cytotoxicity but it may also prompt adaptive immune responses by the activation of cytotoxic T activity [7][8][9][10][11][12][13]. Whereas HLA-E expression usually occurs at low levels [9], this molecule is widely http://dx.doi.org/10.1016/j.humimm.2015.06.016 0198-8859/Ó 2015 American Society for Histocompatibility and Immunogenetics.…”
Section: Introductionmentioning
confidence: 99%